Future research directions - Burt, C.; Caccetta, Louis (2018)
© 2018, Springer International Publishing AG. In this book we have presented a comprehensive account of the mathematical based computational models that have been developed for determining the optimal truck-loader selection strategy for use in large and complex mining operations. We have reviewed the methodology developed over the past 50 years from the early ad hoc spreadsheet approaches to the current highly sophisticated and accurate mathematical based computational models. Our approach has been motivated and illustrated by real case studies provided by our industry collaborators. This final chapter discusses a number of open problems that provide important challenges to the research community.